Cloud Security: Threats, Attacks and Mitigation - Chauhan, KK; Sanger, AKS (International Journal of Computer Sciences and Engineering, 2025)
With tremendous growth of cloud computing in IT industries, cloud security has become one of the major issues that garnered noticeable attention of researchers from industries as well as academia. Cloud computing technology is vulnerable to number of security threats and attacks. Security challenges are major barriers in the adaptation of cloud computing model. Security issues are related to virtualization, network and data including eavesdropping, masquerading, privacy, confidentiality, availability of resources, access control, and identity management. In cloud computing, data are stored on a remote server and accessed through public network. Many of the cryptographic based solutions such as encryption/decryption and digital signature for authentication have been developed. In this paper, we have identified and discussed number of security issues such as authentication, access control, data confidentiality, data integrity, identity management, legal and contractual issues, data breaches, data theft, and unavailability. Moreover, we have also discussed some possible solutions to the security issues and their feasibility and security analysis in real time cloud environment.